A LEXICAL-FUNCTIONAL GRAMMAR REPRESENTATION OF INDONESIAN VERBAL SENTENCES - Fuad Cholisi (Jurnal Sosial Humaniora, 2025)
This paper presents a Lexical-Functional Grammar (LFG) description of Indonesian structures with a verbal predicate. The similarity of Indonesian and English in this type of construction has enabled the application of the original patterns of LFG for the English structures on its Indonesian counterparts. However, some adjustment has to be made in the description of the constituent structure (c-structure). The Indonesian constituent structure here is unique in that whilst it is organized endocentrically, it uses lexocentric means of function identification. Another different feature description that distinguishes the Indonesian LFG representation from the English one is the absence of the features for tense and agreement in the feature structure (f-structure) due to the fact that Indonesian structures are not subject to tense and number agreement. The number feature, however, appears in the cstructure merely to show the status of the subject in terms of singularity or plurality. In addition to the distinctive descriptions above, some constraints and thematic arguments based on the Lexical Mapping Theory have to be applied in the phrase structure rules to accommodate some peculiar characteristics of Indonesian verbal structures, such as those dealing with the position of adjuncts and oblique objects.